2020
DOI: 10.3390/molecules25143214
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Applicability of MALDI-TOF MS as an Alternative Stock Identification Method in a Cryptic Species Complex

Abstract: Knowledge of intraspecific variability of a certain species is essential for their long-term survival and for the development of conservation plans. Nowadays, molecular/genetic methods are the most frequently used for this purpose. Although, the Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) technique has become a promising alternative tool to specify intraspecific variability, there is a lack of information about the limitations of this method, and some methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
4
5
0
Order By: Relevance
“…We interpret the high similarity between the different H . bicuspis species found in this study as a reflection of recent or ongoing speciation processes, as reported in fishes (Maasz et al, 2020; Takács et al, 2014). It is likely that young species are both morphologically and physiologically cryptic, revealing the limit of proteomic fingerprinting for species identification in such instances.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We interpret the high similarity between the different H . bicuspis species found in this study as a reflection of recent or ongoing speciation processes, as reported in fishes (Maasz et al, 2020; Takács et al, 2014). It is likely that young species are both morphologically and physiologically cryptic, revealing the limit of proteomic fingerprinting for species identification in such instances.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, it remains unanswered whether the higher similarity of putative species IV and V results from very similar environmental impacts and thus comparable selection pressures in the past causing a similar physiological response. We interpret the high similarity between the different H. bicuspis species found in this study as a reflection of recent or ongoing speciation processes, as reported in fishes (Maasz et al, 2020;Takács et al, 2014). It is likely that young species are both morphologically and physiologically cryptic, revealing the limit of proteomic fingerprinting for species identification in such instances.…”
Section: Cryptic Diversity and Species Distributionssupporting
confidence: 71%
“…We interpret the high similarity between the differentH. bicuspis species found in this study as a reflection of recent or ongoing speciation processes, as reported in fishes (Takács et al, 2014, Maasz et al, 2020. It is likely that young species are both morphologically and physiologically cryptic, revealing the limit of proteomic fingerprinting for species identification in such instances.…”
Section: Cryptic Diversity and Species Distributionssupporting
confidence: 79%
“…Until now, various factors which could affect difference in spectra such as fixative solution and storage period after fixation have been investigated (Rossel and Martínez Arbizu, 2018). Usefulness of MALDI-TOF MS in cryptic species identification such as bacteria, mosquitoes, fish and sandflies have also been documented (Müller et al, 2013;Dieme et al, 2014;Paauw et al, 2015;Chavy et al, 2019;Maasz et al, 2020). This study further expands on the usefulness of MALDI-TOF MS, confirming that higher-resolution species identification (identification of cryptic species) is possible for copepods as well.…”
Section: Discussion Maldi-tof Mssupporting
confidence: 60%